Synthesis and Characterization of PVA-Enzyme/GA/PPy/ PVC-KTpClPB-o-NPOE Indicator Electrodes, XRD Analysis, FTIR and Variable Signal Analysis - Abd Hakim S (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to synthesize and characterize PVA-Enzyme/GA/PPy/PVC-KTpClPB-o-NPOE indicator indicator electrodes, XRD and FTIR analysis and variable signal analysis for urea sensors. The method used is biosensor potentiometry with urease enzyme immobilization technique which analytes urea. Modify 6 mg of enzyme from the amount of 1 drop and 3 drops in 0.5 mL (50% water: 50% ethanol) in PVA solution and o-NPOE plasticizer in PVC-KTpClPB. The indicator electrode is designed in multi-membrane, namely PVA-Enzyme/GA/PPy/PVC-KTpClPB-o-NPOE. PPy was dissolved in H2SO4 at a concentration of 8 M. Modification of PVA-Enzyme/(GA 2.9%)/PVC-KTpClPB-(o-NPOE 61%) was carried out in one layer each. The number of enzyme drops to see the difference in the intensity of the XRD diffraction spectrum and the difference in the transmittance of the FTIR spectrum from the indicator electrode with multi membrane modified PPy with H2SO4 denoted H2SO4-1 and H2SO4-3, respectively. The best results were obtained on the indicator electrode with the notation H2SO4-1